PENINGKATAN HASIL BELAJAR DAN KEMAMPUAN BERKOMUNIKASI PESERTA DIDIK KELAS V MIN 1 KOTA TASIKMALAYA PADA MATERI SISTEM TUBUH MELALUI MODEL PEMBELAJARAN CARD SORT - Heni Purwitri (Madaris: Jurnal Guru Inovatif, 2022)
This study aims to determine the increase in activity and learning outcomes after the implementation of learning model Card Sort. This research is a classroom action research (PTK) is conducted in two cycles. The subjects were students of class V MIN 1 Kota Tasikmalaya totaling 20 pupils. Collecting data using observation method for learning activities and methods of testing for learning outcomes. Data were analyzed to determine the mean percentage. The results showed that an increase in the percentage of learning activities and learning outcomes. At the first I cycle average percentage of students learning outcomes amounted to 75,04% (middle category) and learning activities amounted to 50% (low category). At the second cycle the average percentage of students learning outcomes amounted to 94,05% (middle category) and learning activities amounted to 87,50% (high category). The implementation of card sort prove to increase the level of learning outcomes significantly and be able to improve students’s activities.